Differences in Perspectives Between Experts and Residents on Living Heritage: A Study of Traditional Chinese Villages in the Luzhong Region - Xiaofeng Shi; Beau B. Beza; Chunlu Liu; Binglu Wu; Ning Qiu (Buildings)
The differences in the heritage perspectives of key stakeholders form an indispensable basis for formulating appropriate conservation strategies for living heritage. However, in existing practices, the differences in heritage perspectives between experts and local residents, who are both key stakeholders, often arise from expert experiences rather than being accurately measured. This study regarded traditional Chinese villages in the Luzhong region as a living heritage case for investigation and quantified such differences. Initially, this study provided a comprehensive description of living heritage using four dimensions: heritage value, heritage attributes, heritage composition, and heritage characteristics. Subsequently, a questionnaire tailored to traditional Chinese villages was developed, and a survey was conducted in the sample villages, resulting in 394 valid responses. According to the Pearson chi-square tests, the findings suggest that expert and local resident respondents showed slight disagreement regarding heritage attributes (x2 = 5.619); however, they presented varying degrees of differences concerning heritage value (x2 = 36.066) and heritage composition (x2 = 36.525), accompanied by distinct preferences. Furthermore, significant discrepancies were evident regarding heritage characteristics. Regarding the four aspects of heritage characteristics, there was a slight difference in the symbiosis of heritage elements (x2 = 3.877) but significant differences in the local resident as a heritage element (x2 = 36.525); there was a minor difference in vitality and continuity (x2 = 3.709) but a rare contradiction for integrity (x2 = 47.649). This study can furnish case data support for surmounting the drawbacks of blindly relying on expert experiences, particularly by integrating local perspectives to safeguard living heritage globally.